Morphometrics and Management of Chinese Citrus Fly, Bactrocera minax (Enderlein) (Diptera: Tephritidae) in Kathmandu, Nepal - Basnet, Bidhika; Thapa, Ashmit; Aryal, Purnika; Shrestha, Subekshya; Adhikari, Debraj (Nepalese Journal of Agricultural Sciences, 2025)
The study was performed at the citrus orchard of Chhahari Retreat in Budhanilkantha, Kathmandu, examined the morphological measurements of both pupa and adult of Bactrocera minax, with a study from March to July 2023. The average pupal length of the Chinese citrus fly determined 9.44 ± 0.10 mm, with a corresponding breadth of 4.33 ± 0.09 mm and weight of 0.051 ± 0.002 gm. Notably, the body length of adult female B. minax surpassed that of males, measuring at 13.9 ± 0.20 mm compared to 11.93 ± 0.33 mm for males, while females exhibited broader bodies (3.92 ± 0.06 mm) in contrast to males (3.18 ± 0.05 mm). Furthermore, adult females displayed a wider wingspan (22.21 ± 0.23 mm) relative to adult males (21.36 ± 0.30 mm), along with longer wings (9.22 ± 0.16 mm) compared to males (8.86 ± 0.16 mm). The ovipositor length was 4.62 ± 0.62 mm. The average weight of female adults calculated 0.0228 ± 0.001 gm, whereas male adults exhibited an average weight of 0.0141 ± 0.002 gm. This research emphasizes significant morphological differences between male and female flies. Furthermore, an attempt was made to manage this pest through the implementation of Area-wide Control Program (AWCP), involving the application of a lethal protein bait comprising 25% protein hydrolysate and 0.1% abamectin (Great fruit fly bait), through spot application at weekly intervals from 8th May to 24th July 2023. A notable decline in fruit loss was observed, decreasing to 1.24% from the previously recorded 27.68% during the 2023 harvest season. This substantial reduction in overall fruit loss, amounting to a noteworthy 26.44% decrease in comparison to 2022 (p<0.00), was effectively attained.